Analyzing the impact of constructing a bypass on traffic network in Darbandikhan town, Kurdistan Region, Iraq - Hasan Ahmad, Imran; Neimat Azeez, Salim; Mahmood Amin Rahimi, Iraj (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Drabandikhan town, which is located within the main road between Suleimani and south of Iraq, suffers from high through traffic volume. Oil tankers and trucks that use urban streets have a negative impact on infrastructure, traffic flow and quality of life in the town. On the daily bases around 800 heavy trucks use the urban distributer network. It is also worth mentioned that Darbandikhan is a tourist area due to the agricultural and topographically nature of the lands and the picturesque views but lack of accessibility created long term impact on tourism market. In order to improve traffic and its negative consequences in the city in terms of environmental, social and economic sustainability, a bypass was proposed to be built to divert traffic (Traffic that does not have a destination in a town) from built-up area and separate it from local traffic. To predict the outcome for the proposed scenario for the decision makers, modeling of the traffic situation is needed. There is several traffic modeling software to do that but The MOVE Meter was used as a modeling tool to analyses the current urban transport in Darbandikhan and to forecast the impact of future change. Move Meter is a tool developed in the Netherlands for urban areas and it is used by almost all Dutch municipalities. Based on the outcome of the research, this bypass is essential as backbone for the traffic system in and around Darbandikhan. By building it more than 50% of the through traffic will divert to it, not only the trucks but also private cars which has no origin and destination in the town and it leads to ease traffic circulation in the town. The public sector has been informed about the outcome of this research and positive impact of realization of this project as well as the challenges.